SYSTEMATIC LITERATURE REVIEW: BAGAIMANA PEMBELAJARAN GEOMETRI 3D DENGAN BERBANTUAN GEOGEBRA - Asmarani Khoirunnisa; Devia Nur Oktaviani; Usman Aripin (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The rapid development of technology can support progress in the field of education, including in mathematics learning. Geogebra is one of the media that can be used in learning, especially in 3D geomtery learning. The purpose of this research with Systematic Literature Review is to provide a description and help solve deeper problems in students' computational abilities when using math software. Acquisition of data through Publish or Perish which contains a Google Scholar database that is reviewed from 200 articles related to 3D geometry learning published in the period 2020-2024 identified by SINTA that can be accessed and is not a foreign language and original research with a final usable 30 articles. The results showed information that learning by using Geogebra is very influential and effective, efficient, and significant so that there is an influence on improving student learning